2007
DOI: 10.1161/circulationaha.106.675355
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Visceral and Subcutaneous Adipose Tissue Compartments

Abstract: Background-Visceral adipose tissue (VAT) compartments may confer increased metabolic risk. The incremental utility of measuring both visceral and subcutaneous abdominal adipose tissue (SAT) in association with metabolic risk factors and underlying heritability has not been well described in a population-based setting. Methods and Results-Participants (nϭ3001) were drawn from the Framingham Heart Study (48% women; mean age, 50 years), were free of clinical cardiovascular disease, and underwent multidetector com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

58
1,163
8
26

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,433 publications
(1,255 citation statements)
references
References 78 publications
58
1,163
8
26
Order By: Relevance
“…However, the sex difference of SFV and VFV has not been fully investigated. Fox et al 13. compared the partial (not total) abdominal visceral and subcutaneous fat volumes in 1,649 men and 1,452 women from the Framingham Heart Study cohort by analyzing a region of 125 mm above S1 on CT scans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the sex difference of SFV and VFV has not been fully investigated. Fox et al 13. compared the partial (not total) abdominal visceral and subcutaneous fat volumes in 1,649 men and 1,452 women from the Framingham Heart Study cohort by analyzing a region of 125 mm above S1 on CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…Although the VFA at the umbilicus has been widely used to identify visceral obesity13, 14, 15, 16, 17, 18, 19, we previously showed that the maximal VFA was not at the umbilicus, but was widely distributed from L1 to L520, 21.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Baseline characteristics were compared between nonhypertension and hypertension groups by the Wilcoxon rank sum test and Z statistic for continuous variables and by the χ 2 test and χ 2 statistic for categorical variables. According to previous studies, there were significant differences in the relationship of total body fat and hypertension between men and women 33, 34. Therefore, Cox regressions were stratified by sex, with hypertension as the end event and the time interval between baseline and hypertension diagnosis as the time variable, and the χ 2 statistic was used to test the regression coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…Fox et al (29) analyzed SATand visceral adipose tissue in individuals without known CAD and found that SAT and VAT were significantly associated with blood pressure, fasting plasma glucose, triglycerides, and high-density lipoprotein, with increased odds of hypertension, impaired fasting glucose, and metabolic syndrome in both genders. VAT was more strongly correlated with most metabolic risk factors than was SAT.…”
Section: Adipose Tissue and Coronary Atherosclerosismentioning
confidence: 99%